36th Annual Hawaii International Conference on System Sciences, 2003. Proceedings of The 2003
DOI: 10.1109/hicss.2003.1174262
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning and innovation in high-tech small firms

Abstract: This paper explores the influence of the processes of learning in organizations on innovation performance in high-tech small firms. After reviewing the literature on learning and innovation, the paper defines the concepts of knowledge management and organizational learning and how they are interlinked. Hypotheses on the link between organizational learning and innovation are presented. An original construct, based on 5 dimensions, is derived to evaluate the degree of organizational learning. The validities (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
0
28
0
4
Order By: Relevance
“…Senge (1992) defines the learning organization as the comprising of a group of people continue to enhance their capacity to create what they aspire. OL is a crucial concept for organizations to sustain and achieve a competitive advantage and a nucleus in organizational innovation (Bukowitz & Williams, 1999;Liao & Wu, 2010;Nonaka & Von Krogh, 2009;Therin, 2003;Wang & Xu, 2018). Jerez-Gomez, Cespedes-Lorente, and Valle-Cabrera (2005) state that knowledge and, more specifically, its acquisition or creation, along with its dissemination and integration within the organization, become a key strategic resource to OL.…”
Section: Km and Organizational Learningmentioning
confidence: 99%
“…Senge (1992) defines the learning organization as the comprising of a group of people continue to enhance their capacity to create what they aspire. OL is a crucial concept for organizations to sustain and achieve a competitive advantage and a nucleus in organizational innovation (Bukowitz & Williams, 1999;Liao & Wu, 2010;Nonaka & Von Krogh, 2009;Therin, 2003;Wang & Xu, 2018). Jerez-Gomez, Cespedes-Lorente, and Valle-Cabrera (2005) state that knowledge and, more specifically, its acquisition or creation, along with its dissemination and integration within the organization, become a key strategic resource to OL.…”
Section: Km and Organizational Learningmentioning
confidence: 99%
“…Örgüt kültürü, örgütsel öğrenme ve yenilikçilik arasındaki ilişki yazında ikili olarak oldukça incelenmiştir (Uğurlu ve Kurt, 2016;Kızıloğlu, 2015;Lee ve Chen, 2015;Zhu, 2015;Maktabi ve Khazaei, 2014;Büschgens, Bausch ve Balkin, 2013;Özdevecioğlu ve Biçkes, 2012;Wanto ve Suryasaputra, 2012;Salim ve Sulaiman, 2011;Ghorbani ve Sabbagh, 2010;Garrido ve Camarero, 884 2010;Joseph ve Dai, 2009;Ando, 2002;Therin, 2002;Hurley, Tomas ve Hult, 1996). Yazındaki bu çalışmalar, örgüt kültürü ve örgütsel öğrenmenin yenilikçilik üzerinde etkisini ampirik olarak ortaya koymuştur.…”
Section: Kavramsal çErçeveunclassified
“…2013;Zhu, 2015). Örgütsel öğrenmenin örgütsel yenilikçilik üzerindeki etkisi de yine yazınla (Garrido ve Camarero,KAÜİİBFD 10(20), 2019: 881-908 903 2010; Özdevecioğlu ve Biçkes, 2012;Salim ve Sulaiman, 2011;Therin, 2002) paralelik göstermektedir. Örgüt kültürünün örgütsel yenilikçilik üzerindeki doğrudan etkisi, örgütsel öğrenme üzerinden olan etkisinden daha fazla olduğu görülmektedir.…”
Section: çAlışmanın Sonunda;unclassified
“…Schein (2010) found that organization with organizational learning would experience a sustainable process to develop good capacity and performance for the better future. Therin (2003) said that organizational learning has a positive relationship with financial performance. Also declared by Suwasono (2006), members of milk cooperatives in East Java shall be cohesive in creating synergy and producing intensive communication, mainly with the prime of milk cooperatives in East Java, respectively GKSI.…”
Section: Contribution Of Market Orientation On Business Unit Performancementioning
confidence: 99%